2021
DOI: 10.1093/rheumatology/keab050
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of anti-CarP and anti-PAD3 antibodies alone or in combination with RF and ACPA for the severity of rheumatoid arthritis

Abstract: Objectives To analyse the predictive value of anti-carbamylated protein (anti-CarP) and anti-peptidyl-arginine deiminase type-3 (anti-PAD3) antibodies, alone or in combination with rheumatoid factors (RFs) and anti-citrullinated protein antibodies (ACPA), to identify patients at high risk of developing severe rheumatoid arthritis (RA) outcomes. Methods Patients within the « Swiss Clinical Quality Management » registry with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
10
2
Order By: Relevance
“…Collectively, studies show that seropositivity for various autoantibodies in RA is associated with a more severe disease course, radiographic damage and bone loss, even prior to the disease onset [90,139,140]. In a recent observational study, various AMPA (to citrullinated, carbamylated, and acetylated peptides) were shown to contribute to the risk of radiographic progression only if present as a combination but not separately [95].…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 99%
“…Collectively, studies show that seropositivity for various autoantibodies in RA is associated with a more severe disease course, radiographic damage and bone loss, even prior to the disease onset [90,139,140]. In a recent observational study, various AMPA (to citrullinated, carbamylated, and acetylated peptides) were shown to contribute to the risk of radiographic progression only if present as a combination but not separately [95].…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 99%
“…In marked contrast with RA, the prevalence of these antibodies in the serum of AS patients is very low (2-4% for ACPAs and 10-20% for anti-CarP antibodies). Therefore, the diagnostic/prognostic value of ACPAs and anti-CarP antibodies is also rather limited in AS, compared to RA [99][100][101]144].…”
Section: Antibodies Directed Against Modified Self-proteins and Self-...mentioning
confidence: 99%
“…This is the case, for instance, of autoantibodies against carbamylated proteins (anti-CarP), reported to be present in 10-15% of RF and ACPA double-negative patients [102,103]. In contrast with the wellestablished clinical and pathogenetic role of ACPA [104,105], the significance of anti-CarP in the context of ACPA negativity remains controversial [106][107][108]. Still, the strong and specific association of HLA-B*08 carrying aspartate at position 9 with anti-CarP but not ACPA [109] reinforces the concept that the spectrum of autoimmunity in RA is broader than that traditionally recognized.…”
Section: Autoantibodiesmentioning
confidence: 99%